Multinucleon Transfer Reactions in the 70Zn (15 MeV/nucleon) + 64Ni System: Detailed Studies of the Reaction Mechanism - Koulouris, Stergios; Souliotis, Georgios; Cappuzzello, Francesco; Carbone, Diana; Pakou, Athina; Agodi, Clementina; Brischetto, Giuseppe; Calabrese, Salvatore; Cavallaro, Manuela; Ciraldo, Irene; Fasoula, Olga; Klimo, Jozef; et al. (HNPS Advances in Nuclear Physics, 2024)
The present work constitutes one of the few high-resolution mass spectrometric studies in the energy range of 15–25 MeV/nucleon in order to produce and identify neutron-rich projectile-like fragments from the reaction of 70Zn (15 MeV/nucleon) + 64Ni. We obtained high-quality experimental data from a recent experiment with the MAGNEX spectrometer at the INFN-LNS in Catania, Italy. The momentum distributions (p/A), angular distributions and the production cross sections of various multinucleon transfer channels were studied thoroughly. Our experimental distributions shown in this contribution are compared with two dynamical models, the Deep-Inelastic Transfer (DIT) model and the Constrained Molecular Dynamics (CoMD) model. Subsequently, the code GEMINI is applied for the de-excitation of the primary fragments. The DIT model, designed to describe the sequential exchange of nucleons, yielded an overall fair description of the processes that correspond to nucleon exchange, but is not able to effectively describe parts of the distributions that refer to direct reaction mechanisms. The microscopic CoMD model calculations indicate that further optimization is needed, that is currently underway. The present work outlines an experimental approach to study peripheral reactions of medium-mass nuclei in the Fermi energy regime and an effort to pave a systematic way toward the efficient production of exotic neutron-rich nuclei.